The Fund's Role Regarding Cross-Border Capital Flows. (Policy Papers; Policy Paper, 2010)
Global capital flows have multiplied many times over in recent years, mainly between advanced economies but increasingly also to emerging markets, reflecting the general reduction in regulatory and informational barriers. Thus, with international asset positions now dwarfing output, global portfolio allocations and reallocations have profound effects on the world economy, as demonstrated by recent boombust episodes of both global reach (e.g., the transmission of the 2001 IT shock and the 2008 mortgage market shock from the United States) and regional significance (in Asia, Latin America, and Central and Eastern Europe). Such cycles and reversals in cross-border capital flows should not be surprising, given that these flows - more so than domestic ones - imply crossing informational barriers, currency and macroeconomic risks, and regulatory regimes.